Paraparesis and paraesthesia following a black ant sting - Norah Alobaid; Majed Alanazi; Sultan Aleshaiwi; Abdulrahman Alhassan (European Journal of Case Reports in Internal Medicine)
Hymenoptera stings can lead to a different range of local and systemic reactions. However, rare and unexpected reactions can develop and may be life threatening. In this paper, we present a 29-year-old female who developed anaphylactic shock followed by paraparesis and paraesthesia after a black ant sting. Her symptoms completely resolved after treatment with plasma exchange. Several studies have linked these neurological complications to delayed immunological reactions that are triggered by insect antigen.